Muscle-Specific Effects of Genotype, Animal Age, and Wet Aging Duration on Beef Color, Tenderness, and Sensory Characteristics - Muhammad Kashif Yar; Muhammad Hayat Jaspal; Sher Ali; Iftikhar Hussain Badar; Muawuz Ijaz; Jibran Hussain (Animals)
This study investigated the effects of genotype, animal age, muscle type, and aging duration on meat quality characteristics of Psoas major (PM), Longissimus thoracis (LT), Longissimus lumborum (LL), and Gluteus Medius (GM) muscles. The PM, LT, LL, and GM muscles were sourced from a total of 32 bulls, consisting of 16 humped (Bos indicus) and 16 humpless (Bos indicus × Bos taurus) bulls aged 21 ± 2 and 30 ± 3 months. The muscles underwent aging durations of 0, 7, and 14 days. Meat pH, color, drip loss, cooking loss, instrumental shear force, lipid oxidation (thiobarbituric acid reactive substances/TBARS), and sensory analysis were performed. Our results indicated that humped bulls had superior color, while humpless bulls exhibited better sensory characteristics. The 30 ± 3 months of age bulls showed improved color and sensory characteristics with higher TBARs values than the 21 ± 2 months of age bulls. The color, tenderness, and sensory characteristics improved in PM and LT at 7 days, whereas in LL and GM they improved at 14 days. PM showed better tenderness and overall acceptability among different muscles, while LL showed better color and oxidative stability. This study suggested the necessity of muscle-specific aging strategies to enhance the meat quality characteristics of humped and humpless bulls. Further research could explore additional aging durations and other muscle types to better understand their impact on meat quality characteristics.